2022
DOI: 10.1097/bor.0000000000000897
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in elucidating the genetic basis of systemic sclerosis

Abstract: Purpose of reviewSystemic sclerosis (SSc) is a complex autoimmune disorder that affects the connective tissue and causes severe vascular damage and fibrosis of the skin and internal organs. There are recent advances in the field that apply novel methods to high throughput genotype information of thousands of patients with SSc and provide promising results towards the use of genomic data to help SSc diagnosis and clinical care.Recent findingsThis review addresses the development of the first SSc genomic risk sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In addition, genetic factor studies at different levels of genetic information have advanced considerably with the development of technology and lower costs. There is a close relationship between human leukocyte antigen (HLA) locus genes and SSc, and 32 non-HLA loci have been identified (4). This opens up promising possibilities for the use of precision medicine for SSc patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, genetic factor studies at different levels of genetic information have advanced considerably with the development of technology and lower costs. There is a close relationship between human leukocyte antigen (HLA) locus genes and SSc, and 32 non-HLA loci have been identified (4). This opens up promising possibilities for the use of precision medicine for SSc patients.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic modifications are known to play a significant role in SSc pathogenesis, but taken alone they do not allow clarification of the occurrence of the disease [ 59 , 60 ]. Indeed, SSc is thought to be determined by complex interactions between genetic predispositions and epigenetic modifications such as DNA methylation, histone modifications, and microRNAs (miRNAs), which are able to regulate gene expression without altering the DNA sequence [ 61 , 62 , 63 ].…”
Section: Genetic and Epigenetic Mechanisms Involved In Ssc Defective ...mentioning
confidence: 99%
“…Indeed, SSc is thought to be determined by complex interactions between genetic predispositions and epigenetic modifications such as DNA methylation, histone modifications, and microRNAs (miRNAs), which are able to regulate gene expression without altering the DNA sequence [ 61 , 62 , 63 ]. In the last two decades, besides the known contribution of human leukocyte antigen (HLA) class II haplotypes to the risk of developing SSc, various multicenter studies discovered several non-HLA loci contributing to SSc pathogenesis, but very few pointed toward potential genetic modifications relevant for disease vasculopathy [ 59 , 60 ]. In 2020, Takagi et al genotyped four single nucleotide polymorphisms of the HIF1A gene in a Japanese SSc population and found that the AA genotype at rs12434438 was not only significantly increased in SSc patients with PAH compared to those without but also associated with the severity of this pulmonary condition [ 64 ].…”
Section: Genetic and Epigenetic Mechanisms Involved In Ssc Defective ...mentioning
confidence: 99%
“…In addition, the disease represents a real social burden owing to its heavy impact on facial appearance, orofacial functions, and everyday life activities [ 3 ]. Although the etiology of SSc remains unknown, a large body of evidence now indicates that genetic susceptibility factors have an essential role in the onset and the evolution of this disease [ 4 ]. In recent years, there have been substantial advances in the understanding of SSc pathogenesis, as well as in early diagnosis and clinical management of patients.…”
mentioning
confidence: 99%